1999
DOI: 10.1590/s0004-282x1999000100006
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de pacientes submetidos a cirurgia de epilepsia

Abstract: RESUMO -Epilepsia refratária ao tratamento medicamentoso é condição que interfere direta e negativamente na qualidade de vida dos pacientes, dificultando-lhes principalmente a integração social. O tratamento cirúrgico tem se mostrado eficaz no controle das crises em casos refratários, ocupando lugar importante no tratamento das epilepsias. Avaliamos a qualidade de vida de pacientes epilépticos, antes e após o tratamento cirúrgico, através de um questionário sobre qualidade de vida, adaptado do QOLIE-10 aplicad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
1
5
0
3
Order By: Relevance
“…With respect to the overall outcome of QOL, the survey found that almost all patients showed significant improvement, which concurs with other results 3,14,[16][17][18][22][23][24][25][26][27] . Despite the excellent control of seizures, only one of our patients had a decrease in the overall QOL score (subject 13), mainly due to social, school and behavioral factors.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…With respect to the overall outcome of QOL, the survey found that almost all patients showed significant improvement, which concurs with other results 3,14,[16][17][18][22][23][24][25][26][27] . Despite the excellent control of seizures, only one of our patients had a decrease in the overall QOL score (subject 13), mainly due to social, school and behavioral factors.…”
Section: Discussionsupporting
confidence: 88%
“…Due to the seizures and their chronic characteristic, epilepsy is a condition that changes the life of the patients both physically and psychosocially. Therefore, concern about quality of life (QOL) of the patients is increasing 1,3 . Quality of life is defined as the perception by the patient of his/her own physical, mental, emotional and social well-being, and his/her perception of how the disease has altered his/ her life 4 .…”
mentioning
confidence: 99%
See 3 more Smart Citations